The effect of good corporate governance on banking profitability - Vicente Ramos, Wagner Enoc (2020)
The objective of this paper is to determine the impact of the variables of good corporate governance on profitability by equity of the banks of Peru during the period 2009 - 2018. The regression analysis of panel data was applied on a sample of 13 banks in Peru listed on the Lima Stock Exchange. Through an econometrics model it was obtained as a result that there was a significant direct relationship between the general meeting of shareholders and return on equity (p <0.05), which indicates that, the greater the integration of the General Meeting of shareholders in banking companies, the greater the profitability of equity for shareholders; which also shows that, the greater the transparency of information, the greater the profitability of equity for shareholders. This evidence provides beneficial information for supervisory authorities, stakeholders and academics.